Practice size, financial sharing and quality of care - Devlin, Rose A; Hogg, William; Zhong, Jianwei; Shortt, Michael; Dahrouge, Simone; Russell, Grant (Université d'Ottawa | University of Ottawa, 2013)
Abstract Background Although we are observing a general move towards larger primary care practices, surprisingly little is known about the influence of key components of practice organization on primary care. We aimed to determine the relationships between practice size, and revenue sharing agreements, and quality of care. Methods As part of a large cross sectional study, group practices were randomly selected from different primary care service delivery models in Ontario. Patient surveys and chart reviews were used to assess quality of care. Multilevel regressions controlled for patient, provider and practice characteristics. Results Positive statistically significant associations were found between the logarithm of group size and access, comprehensiveness, and disease prevention. Negative significant associations were found between logarithm group size and continuity. No differences were found for chronic disease management and health promotion. Practices that shared revenues were found to deliver superior health promotion compared to those who did not. Interacting group size with the presence of a revenue-sharing arrangement had a negative impact on health promotion. Conclusions Despite the limitations of our study, our findings have provided preliminary evidence of the tradeoffs inherent with increasing practice size. Larger group size is associated with better access and comprehensiveness but worse continuity of care. Revenue sharing in group practices was associated with higher health promotion compared to sharing only common costs. Further work is required to better inform policy makers and practitioners as to whether the pattern revealed in larger practices mitigates any of the previously reported benefits of continuity of primary care. We found few benefits of revenue sharing – even then the effect of revenue sharing on health promotion seemed diminished in larger practices.